Figures of Southeast Asian Modernity - Lindquist, Johan; Harms, Erik (Anthropologist); Barker, Joshua, 1967- (Book collections on Project MUSE., 2014)
This book brings together the fieldwork of over eighty scholars and covers the nine major countries of the region: Burma (Myanmar), Cambodia, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. An introduction outlines important social transformations in Southeast Asia and key theoretical and methodological innovations that result from ethnographic attention to the study of key figures. Each section begins with an introduction by a country editor followed by short essays offering vivid and intimate portraits set against the background of contemporary Southeast Asia. The result is a volume that combines scholarly rigor with a meaningful portrayal of a region of the world undergoing rapid change. A reference bibliography offers suggestions for further reading. -- Publisher's description.